Photosynthesis in seedling, juvenile and adult of oil palm (elaeis guineensis) - Kingkaew Apichatmeta (Prince of Songkla University, 2018)
Thesis (M.Sc., (Technology and Environmental Management)) Prince of Songkla University, 2016